2017
DOI: 10.3892/ol.2017.5982
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑proliferative and anti‑metastasis effects of ten oligostilbenes from the seeds of Paeonia suffruticosa on human cancer cells

Abstract: Abstract. Paeonia suffruticosa from the section Moutan of the genus Paeonia is an important Chinese medicinal herb. In our previous study, 10 oligostilbenes from the seeds of P. suffruticosa, including trans-resveratrol and its dimers and trimers, were isolated and identified. In the present study, the anti-proliferative effects of these 10 oligostilbenes were systemically evaluated in a panel of human lung, breast and bone cancer cell lines, and their apoptotic effects were analyzed using a high-content multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…The analysis of their structure-activity relationship revealed that the trans-isomerism is important for their proliferative activity to rabbit OA chondrocytes. Our results suggested that the EC 50 of three cis isomers were significantly higher than their corresponding trans isomer, which agreed with our current knowledge that the trans isomer of natural compounds is a more active form than cis because of its lower steric hindrance [22]. The activity of oligostilbenes to promote chondrocyte proliferation often increased with the degree of polymerization, which was consistent with their structure-antioxidant activity [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of their structure-activity relationship revealed that the trans-isomerism is important for their proliferative activity to rabbit OA chondrocytes. Our results suggested that the EC 50 of three cis isomers were significantly higher than their corresponding trans isomer, which agreed with our current knowledge that the trans isomer of natural compounds is a more active form than cis because of its lower steric hindrance [22]. The activity of oligostilbenes to promote chondrocyte proliferation often increased with the degree of polymerization, which was consistent with their structure-antioxidant activity [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…Paeonia suffruticosa is an important Chinese medicinal herb. Studies by Gao & He (2017) indicate strong antiproliferative and antimetastasizing effect of this species. We observed inhibiting effect of P. suffruticosa for P. vulgaris (6.1 mm).…”
Section: Resultsmentioning
confidence: 81%
“…This compound has been reported to possess antiallergic and anti‐inflammatory properties, as suggested by the decreased cyclooxygenase‐2 expression and reduced production of prostaglandin E 2 by Gnetin‐H–treated mast cells . In addition, its cis and trans forms inhibited the metastatic potential of MDA‐MB‐231 breast cancer cells in vitro and promoted apoptosis in osteosarcoma and breast and lung cancer cell lines via the inhibition of NF‐κB. These effects have also been confirmed in a mouse xenograft tumor model .…”
Section: Gnetin‐hmentioning
confidence: 99%